Library services for young people: current trends - I. V. Tolstoukhova; M. V. Maslakova (Библиосфера)
Currently, youth libraries need radical modernization in the context of global cyberspace and social networks. Taking the challenge of nowadays, rebuilding their age-old traditions, libraries forced to change the format and saturate their space with new meanings.  Studying the organization of modern library services for young people is based on the Information-Library Center for youth of Tyumen city. Evidentlu for it the authors elaborate recommendations to improve servicing young people in the information-library center for youth of Tyumen.  The research theoretical and practical significance is determined by the need for an urgent study of youth activities of library institutions to create a positive experience with this category of users.  To identify the young people attitude to the activity of the Information-Library Center for youth in Tyumen, the authors monitored public opinion with a sociological survey (questionnaire). The survey has revealed: what users want to get from visits; what forms of work they like, and what would they like; what is the comfort of working in the library.  The analysis of the obtained data allowed authors to conclude:  1. Young people are interested in getting comprehensive information on the topics of their interest.  2. Modern technical equipment and the availability of designed work and leisure sites are important components of the library space.  3. The most attractive leisure activities in the Centre include creative meetings, musical or literary events.  4. Respondents attributed the problem of professional growth of specialists, underdeveloped forms of intellectual leisure and types of information support as shortcomings of the Information-Library Center for young people, which are worth paying attention.  5.The most popular sources of information about the Center activities are social networks.  6. Users rated the Center work as 9.4 points in 10-point scale.  The authors have developed measures to improve the quality of library services for young people, increase the interest and activity of this social group in the work of the Information-Library Center for young people. They are:  1. Actualizing the library collection in accordance with youth preferences;  2. Developing advanced forms of book borrow;  3. Organizing the Center library space comfortable for young people;  4. Involving young specialists in library activity;  5. Expanding the library’s social partnership with youth associations.